Coding sequence for the pT181 repC product: a plasmid-coded protein uniquely required for replication. - Novick, R P (1982)
pT181 is a 4.4-kilobase plasmid from Staphylococcus aureus specifying tetracycline resistance and present in about 20 copies per cell. The existence of a diffusible pT181 product required for plasmid replication has been proposed on the basis of trans-complementable thermosensitive mutants defective in plasmid maintenance (phenotype Tsr). In this report, the Tsr mutants are shown to have primary replication defects, and the genetic complementation data are confirmed biochemically. All of five mutations are in a single cistron, the repC cistron; interruption of the plasmid DNA molecule at any of three neighboring restriction sites inactivates repC function. Analysis of the DNA sequence in this region reveals an open reading frame of 939 base pairs which encodes the repC product, a 313-amino acid protein. pT181 replication has been demonstrated in cell-free extracts to require specifically a pT181-coded protein of approximately the same size, and it is proposed that this protein is, indeed, the repC product. Preliminary evidence is discussed suggesting that the pT181 replication rate is controlled at the level of synthesis of the repC protein.